Pelanggaran Prinsip Kerja Sama dalam Wacana Humor Stand Up Comedy Dzawin Nur pada Kanal Youtube Stand Up Kompas Tv Kompetisi SUCI 4 dan Implikasinya terhadap Pembelajaran SMA Teks Anekdot - Zulham Rasidin Indrarrobbika; Petrus Poerwadi; Misnawati Misnawati; Linggua Sanjaya Usop (Universitas Palangka Raya, 2025)
The violation of the cooperative principle in the humor discourse of Dzawin Nur's stand-up comedy, as presented on the YouTube channel Stand Up Kompas TV, particularly in the SUCI 4 competition and anecdotal text implication learning High school. Undergraduate Thesis. Indonesian Language and Literature Education. Department of Language and Arts Education. Faculty of Teacher Training and Education. University of Palangkaraya. This study analyzes the violation of the cooperative principle in the humor discourse of Dzawin Nur's stand-up comedy, as presented on the YouTube channel Stand Up Kompas TV, particularly in the SUCI 4 competition. Grice’s cooperative principle includes the maxims of quantity, quality, relevance, and manner. Violations of these maxims in stand-up comedy create unique humorous effects and capture the audience's attention. This research employs a pragmatic approach using a qualitative descriptive method to identify and analyze cooperative principle violations in Dzawin Nur’s stand-up material. The findings indicate that maxim violations of the cooperative principle found occur in the form of exaggerated information the maxim of quantity (13 data), statements that are not entirely truthful the maxim of quality (19 data), Every contribution in communication must be relevant to the context of the conversation the Maxim of Relevance (18 data) and indirect or overly elaborate expressions the maxim of manner (15 data). These techniques are used to enhance humor, create surprise effects, and strengthen the comedian’s distinctive style in delivering anecdotes. The violation of the cooperative principle in humor discourse not only serves as entertainment but also acts as an effective communication strategy in engaging the audience. The implications of this study for high school anecdotal text learning suggest that understanding cooperative principle violations can help students develop language skills, particularly in writing and analyzing anecdotal texts. By recognizing how humor is constructed through deviations from communication norms, students can be more creative in crafting engaging and effective anecdotes. Additionally, this research provides insights for educators on utilizing stand-up comedy discourse as a contextual and relevant teaching medium that connects with students’ daily lives.